PENERAPAN METODE PERMAINAN CLUE AND LABEL UNTUK MENINGKATKAN KEPERCAYADIRIAN DAN PEMAHAMAN SISWA - Rohyati, Riyanti Siti; Kurnia, Dadang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
ABSTRACTThe learning conditions in class IV of SDN Mandalaherang I were carried out in groups seen from a sitting position every day that had been grouped. But in learning students look less active. In the material of economic activity and its relationship with various fields of work, especially regarding the types of jobs that produce goods and services, students still do not understand the difference between the work that produces goods and services. In addition, students seem to lack confidence in learning activities, seen when delivering the results of the discussion, students seem less confident about the results they have done such as reading in a slow voice. When the teacher gives the opportunity for students to comment on the results of their friends' discussions, most students are only silent, especially women. So it needs improvement in learning activities to improve students' understanding and self-confidence by applying clue and label playing methods. Through the classroom action research method which was conducted for three meetings on learning in class IV on theme 4, sub-theme 2 of learning 1, the assessment of belief, and understanding of students was carried out. In the first cycle for trustworthiness students who achieve interpretation are very good at 39.1%, in the second cycle reached 78.3%, and in the third cycle reached 87%. For understanding related to material about work that produces goods and services each cycle has increased in the first cycle reached 60.9%, the second cycle reached 73.9%, and in the third cycle reached 82.6%.